(3GdfbhO GdPgHjI GdCSHGfjI GdeJOGhdI aj GdCShGb GdeUQjI NdGd GdYUQ Gdeedhcj aj VhA cfR RjfH NGJhf HeJMa Gdaf GdESdGej HGdbGgQI (B/ s - (3QGVjI eMeO YHOGdSejY LGOs; (3CM`eO GdSjO GdUGhj (B: s; (3QCaJ eMeO eMeO GdfHQGhj (B: s; (3UHQj`f YHOGdLjO GdbUGU (B: s ((3GdbGgQI (B: s (3QGVjI eMeO YHOGdSejY LGO (B: s, 2015)
(3JYO gPg GdOQGSI (B" (3GdfbhO GdPgHjI GdESHGfjI GdJj cGfJ eJOGhdI aj GdGShGb GdeUQjI NdGd GdYUQ Gdeedhcj ; aj VhA cfR RjfH NGJhf HeJMa Gdaf GdESdGej(B" (3`ef Cge GdOQGSGJ aj eLGd Yde GdeSchcGJ ; dchfgG JgJe HEdbGA GdVhA Ydi GdfbhO GdPgHjI GdESHGfjI GdJj cGfJ eJOGhdI aj GdCShGb GdeUQjI NdGd GdYUQ Gdeedhcj YGeI (B: (3hGdJj Je GdYKhQ YdjgG aj cfR (B"(3RjfH NGJhf(B" (3HUaI NGUI ; ceG Cf gPG GdehVhY dg CgejI NGUI aj JGQjN GdJOGhd GdfbOj aj aJQI gGeI ef aJQGJ JGQjN eUQ GdESdGejI(B. (3gPG h JJLSO CgejI gPG GdehVhY aj Cfg jYO ef Chdi GdOQGSGJ GdJj JfGhdJ GdfbhO GdESHGfjI aj eUQ aj GdYUQ Gdeedhcj ; hPdc YHQ OQGSI JGQjNjI (B: (3GbJUGOjI (B: (3hJLGQjI ef NdGd QUO eLehYI ef GdfbhO GdPgHjI dHYV GdeeGdc GdESHGfjI GdfUQGfjI ; aVdkG Yf GdOQGSI GdhUajI hGdJMdjdjI dJdc GdfbhO ; GdJj Cecf Gdhbha Ydi Gdbje GdfbOjI dgG ef NdGd ebGQfJgG eY GdfbhO GdeedhcjI GdeYGUQI ; eY GdbGA GdVhA Ydi OhQ Sc GdfbhO GdESHGfjI (B: (3hWQb UfGYJgG hGdbGFejf YdjgG (B: (3hebGQfJgG HOhQ GdSc GdESdGejI(B. (3; cd gPG Yf WQjb JJHY ZGdHjI GdeYdheGJ GdeJfGKQI gfG hgfGc (B: (3hcPdc GdebGdGJ GdJj fTQJ hJJYdb HgPG GdehVhYs
(3GdeLdO GdKGfi YHGQI Yf NQGFW h dhMGJ h CTcGds
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdBKGQ (B- (3bSe GdCKGQ GdESdGejIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GSchOhs; (3OhHd (B- (3GdeVGYas; (3chQhfGs